Efektifitas Penerapan Model Pembelajaran Kooperatif Tipe Teaching Game Team (TGT) Untuk Meningkatkan Keterampilan Berbicara Siswa di Sekolah Menengah Pertama Muhamadiyah 1 Sidoarjo - Apriani, Apriani; Anwar, Najih (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This study aims to analyze the influence of the teaching game team learning model strategy on students' speaking skills in learning Arabic, this type of research is classroom action research, the data is analyzed qualitatively. Observations were made on 20 students who previously analyzed the condition of students' abilities in learning abilities in the classroom. The results of the study showed that the application of the teaching game team type learning model could improve students' understanding of students' morals as seen from 100% completeness in 2 learning cycles. So, it can be concluded that there is influence from the application of the teaching game team cooperative model to increase students' maharah kalam.